2018
DOI: 10.5812/erms.80301
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Direct Observation of Procedural Skills Assessment Method on Clinical Performance of Radiology Students

Abstract: Background and Objectives: Assessment is one of the most important factors involved in effective medical education. Direct observation of procedural skills (DOPS) assessment method requires direct observation of learners during the performance of clinical procedures on patients and providing appropriate feedback to learners. This research was carried out to evaluate the effect of DOPS assessment method on the clinical performance of radiology students at Kermanshah University of Medical Sciences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Also, a study conducted by Habibi (2013) showed that the use of both DOPS and MINI-CEX methods increased the power of clinical skills during the procedure in nursing students, when compared to traditional methods (22). Tohidnia et al (2018), in their study on radiology students, reported that the clinical performance score was significantly higher in the DOPS assessment method than in the traditional method (23). Also, the improvement of the evaluation phase by the DOPS method compared with the preliminary phase improved clinical performance, which could be due to providing appropriate feedback and eliminating functional weaknesses (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a study conducted by Habibi (2013) showed that the use of both DOPS and MINI-CEX methods increased the power of clinical skills during the procedure in nursing students, when compared to traditional methods (22). Tohidnia et al (2018), in their study on radiology students, reported that the clinical performance score was significantly higher in the DOPS assessment method than in the traditional method (23). Also, the improvement of the evaluation phase by the DOPS method compared with the preliminary phase improved clinical performance, which could be due to providing appropriate feedback and eliminating functional weaknesses (23).…”
Section: Discussionmentioning
confidence: 99%
“…Tohidnia et al (2018), in their study on radiology students, reported that the clinical performance score was significantly higher in the DOPS assessment method than in the traditional method (23). Also, the improvement of the evaluation phase by the DOPS method compared with the preliminary phase improved clinical performance, which could be due to providing appropriate feedback and eliminating functional weaknesses (23).…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Observation and evaluation of learners during performing procedures on patients and giving appropriate feedback to them can thus lead to obtaining and improving skills among them. [ 13 ] Feedback after the direct observation is very meaningful, especially when it addresses a learner's immediate concerns and provides information to the student that leads to improved learning. [ 14 ] The implementation of any of the evaluation tools depends on students' acceptance under its effect.…”
Section: Introductionmentioning
confidence: 99%